Cancer of unknown primary ‐ incidence, mortality trend, and mortality‐to‐incidence ratio is associated with human development index in Central Serbia, 1999–2018: Evidence from the national cancer registry. (20th October 2021) - Ignjatović, Aleksandra; Stojanović, Miodrag; Milošević, Zoran; Anđelković Apostolović, Marija; Filipović, Tamara; Rančić, Nataša; Marković, Roberta; Topalović, Marija; Stojanović, Dijana; Otašević, Suzana
Abstract: Objectives: The aim was to estimate the trend of incidence, mortality and mortality‐to‐incidence ratio (MIR) in Central Serbia in 1999–2018 and its possible association with the human development index (HDI). Methods: In this study, cancer of unknown primary (CUP) was included as C77‐C80 codes. Trend analysis was performed in the Joinpoint Regression Programme version 4.8.0.1. HDI combines life expectancy, educational attainment and gross national income. HDI values for Serbia are extracted from the global bank site. Results: Joinpoint regression analysis of the age‐standardised incidence rate of CUP showed a significantly increasing trend with annual percent change (APC) of 8.5% (95% confidence interval [CI] 3.0–14.3%) in males and 7.8% (95%CI 2.7–13.2) in females. The age‐standardised mortality rate of CUP showed a significantly decreasing trend with APC of −1.7% (95%CI −2.8 to −0.5%) in males and −1.4% (95%CI −2.7 to −0.1%) in females. MIR showed a significantly decreasing trend with APC of −9.3% (95%CI ‐14.6 – −3.6%) in males and −7.1% (95%CI −10.5% to −4.2%) in females. The linear regression showed significant inverse association among HDI and the MIR of CUP in males ( r 2  = 0.464, p  = 0.002) and in females ( r 2  = 0.612, p  < 0.001). Conclusions: Decline of MIR was associated with HDI, suggesting that CUP prognosis follows socio‐economic status.